Trends of gastric cancer burdens attributable to risk factors in China from 2000 to 2050Research in context - Feifan He; Shaoming Wang; Rongshou Zheng; Jianhua Gu; Hongmei Zeng; Kexin Sun; Ru Chen; Li Li; Bingfeng Han; Xinqing Li; Wenqiang Wei; Jie He (Elsevier, 2024)
Summary: Background: The incidence of gastric cancer (GC) decreased in past decades, which was thought largely attributable to risk factors control, yet China still accounts for 44% of global GC burdens. We aimed to estimate changing trajectories of proportions of GC burdens attributable to modifiable risk factors from 2000 to 2050 in China, to inform future targeted preventive strategies. Methods: The incidence and new cases of GC were predicted to 2050 using Bayesian age-period-cohort model based on incidence data by anatomical subsites drawn from 682 cancer registries from National Central Cancer Registry. Population attributable fractions (PAFs) were calculated based on prevalence of risk factors and relative risks with GC. Temporal trends of PAFs were described by sex and categories of risk factors using joinpoint analysis. Findings: We observed declining trends of PAFs of Helicobacter pylori (H. pylori) infection, smoking, pickled vegetable and alcohol consumption, but increasing trends of PAFs of unhealthy body mass index and diabetes for GC in China. The combined PAFs of these risk factors were estimated to decrease by 10.57% from 2000 to 2050 for GC. We estimated there will be 279,707 GC (122,796 cardia gastric cancer [CGC] and 156,911 non-cardia gastric cancer [NCGC]) cases in 2050. Out of these cases, 70.18% of GC cases could be attributable to modifiable risk factors, while H. pylori infection was predicted to be responsible for 40.7% of CGC and 62.1% of NCGC cases in 2050. Interpretation: More than half of GC remained attributable to modifiable risk factors in China. Continued effective strategies on risk factors control are needed to reduce the burden of this highly life-threatening cancer in future. Funding: Beijing Nova Program (No. Z201100006820069), CAMS Innovation Fund for Medical Sciences (CIFMS, grant No. 2021-I2M-1-023), CAMS Innovation Fund for Medical Sciences (CIFMS, grant No. 2021-I2M-1-010), Talent Incentive Program of Cancer Hospital Chinese Academy of Medical Sciences (Hope Star).